Accounting Aspect of Concepts Correlation: Responsibility Centers, Cost Center, Checkpoint of Expenses - Ковалюк, О. М.; Колібаба, О. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Considered and analyzed the concept of responsibility center, cost center, location costs and benchmark costs and their relationship within the administrative account for example the cost of production in the dairy industry. The purpose of the article is a theoretical justification accounting features analyzed concepts. This study is useful for manufacturing companies, allowing them to set breakpoints at certain stages of the process, and track the change in costs in the process or set of homogeneous processes. A expenses under control points considered stages of the production process, which may conduct controls to prevent the risk of going beyond the limits, or to minimize such risk to acceptable levels. Investigated that the conduct accounting responsibility centers, cost centers, sometimes spending or reference points should be used regulatory method of cost accounting. The possibilities go from one checkpoint to another with changing production costs. Studied the principles and elements of internal reporting and the ability to use them in the accounting systems at analyzed terms. The process of domestic cheese production and adaptation of systems of control points analyzed costs in the manufacturing process.